Core-shell type hydrophobic modified activated carbon and preparation method thereof
By covering the outer layer of activated carbon with a porous shell of silica and grafting hydrophobic groups, the core-shell hydrophobic modified activated carbon is solved, and the problem of reducing the adsorption capacity of activated carbon in humid environments is achieved, and more stable hydrophobic properties are achieved. Improved adsorption performance.
Patent Information
- Application Number
- CN202411574956.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-11
AI Technical Summary
In humid environments, the pores of activated carbon are occupied by water molecules, resulting in a reduced adsorption capacity, limiting its application in high humidity environments. The existing hydrophobic modification methods will reduce the specific surface area and stability of activated carbon.
Core-shell hydrophobic modified activated carbon is formed by coating the outer layer of activated carbon with a porous shell of silica and grafting hydrophobic groups on the shell. This method uses control of reaction conditions and hydrolysis of ethyl orthosilicate to form silanol monomers, polymerized on the outer layer of activated carbon, ensuring the improvement of hydrophobicity and adsorption performance.
The activated carbon has achieved good pollutant adsorption performance under water for a long time, and is more stable in hydrophobicity and higher grafting rate, which hardly affects the internal micropore structure and specific surface area of the activated carbon.
Smart Images

Figure CN119409192A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a core-shell type hydrophobically modified activated carbon and also relates to a method for preparing the core-shell type hydrophobically modified activated carbon. Background Art
[0002] Activated carbon is widely used in gas and liquid phase purification. Its key mechanism involves substances entering the activated carbon through surface adsorption and pore diffusion, followed by adsorption, chemical adsorption and physical adsorption in its pores, thereby effectively removing or separating harmful substances in the carrier medium. In gas phase purification, activated carbon can remove harmful gases, odors, volatile organic compounds (VOCs), etc. in the air. In liquid phase purification, activated carbon can remove heavy metal ions, organic matter, drug residues, etc. in water.
[0003] The adsorption capacity of activated carbon is closely dependent on its porous structure. These micropores and mesopores provide a large number of adsorption sites, which can efficiently adsorb harmful substances in gases or liquids. However, in a humid environment, due to the interaction of capillary forces and hydrogen bonds, water molecules also have a strong adsorption capacity, and their small molecular size makes it easier for them to occupy the pores of activated carbon. Therefore, in a humid or aqueous environment, water molecules and target pollutants will compete for adsorption at the adsorption sites of activated carbon, ultimately resulting in the pores of activated carbon being preferentially occupied by water molecules, thereby reducing its adsorption capacity for other substances. This competitive effect severely limits the application of activated carbon in high humidity environments.
[0004] Therefore, when using activated carbon in a humid environment, such as wastewater treatment and humid flue gas capture of VOCs, the activated carbon needs to be hydrophobically modified to alleviate the problem of reduced adsorption capacity of activated carbon. However, the current hydrophobic modification method of activated carbon will greatly reduce the original specific surface area of the activated carbon and the hydrophobic modification is insufficiently stable. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a core-shell type hydrophobically modified activated carbon; another purpose of the present invention is to provide a method for preparing the above-mentioned core-shell type hydrophobically modified activated carbon, which has almost no effect on the micropore structure, pore characteristics and specific surface area inside the activated carbon, and can enable the activated carbon to maintain good pollutant adsorption performance for a long time underwater.
[0006] Technical solution: The core-shell hydrophobically modified activated carbon described in the present invention comprises activated carbon and a porous silica shell layer wrapped around the activated carbon.
[0007] Wherein, the hydrophobic group is one of -(CH3)3, -(C2H5)3, -C3H7 or -C6H5.
[0008] The preparation method of the core-shell hydrophobically modified activated carbon specifically comprises the following steps:
[0009] (1) Construction of silica shell: The pretreated activated carbon is dispersed in a solvent, and ethyl orthosilicate is added thereto. The pH of the reaction solution is first adjusted to 5-6, and stirred at 450-500 r / min and 50-60° C. for 20-30 min. The pH of the reaction solution is then adjusted to 8-9, and stirring is continued for 0.5-1 h to obtain a suspension A. The suspension A is centrifuged to obtain a preliminarily modified activated carbon. The preliminarily modified activated carbon is washed and dried to obtain an intermediate product coated with a hydrophilic silica shell.
[0010] (2) Grafting of hydrophobic groups: dispersing the intermediate product obtained in step (1) in a solvent, adding siloxane thereto, and stirring thoroughly to obtain a suspension B; centrifuging the suspension B to obtain hydrophobically modified activated carbon; and washing and drying the hydrophobically modified activated carbon;
[0011] (3) adding mercaptosilane and the product obtained in step (2) into a solvent, adding hydrogen peroxide after the reaction, and then centrifuging, washing, and drying to obtain a final product.
[0012] The core-shell hydrophobically modified activated carbon obtained by the present invention has the advantages of both hydrophilicity and hydrophobicity: the attraction of the activated carbon surface to aqueous solution is enhanced; and the selective adsorption to organic molecules is enhanced.
[0013] Wherein, in step (1), the pretreatment of the activated carbon is: heating the activated carbon at a temperature not lower than 120° C. for 5 to 8 hours until the quality is stable, so as to remove bound water and adsorbed impurities.
[0014] Wherein, in step (1), the intermediate product obtained is activated carbon coated with a silica shell layer. The intermediate product is activated carbon coated with a layer of silica shell layer, and its hydrophilicity is further enhanced compared with the original activated carbon.
[0015] Wherein, in step (1) and step (2), the solvent is anhydrous ethanol, ethylene glycol or deionized water; when the solvent is deionized water, a surfactant of 0.4% by mass of the solvent is added to the solvent; the surfactant is DuPont surfactant or Liou surfactant.
[0016] Wherein, in step (1), the mass volume ratio of activated carbon to tetraethyl orthosilicate is 1 g: 1-2 mL.
[0017] Wherein, in step (1), the reagents for adjusting pH are hydrochloric acid with a concentration of 0.1 mol / L and ammonia water with a mass fraction of 25-28%.
[0018] Among them, step (2) is hydrophobic modification, and the hydrophobic group is directly grafted onto the hydrophilic silica shell layer, and the hydrophobic shell layer finally obtained is SiO2@-OSiR n , -R nIt is one of -(CH3)3, -(C2H5)3, -C3H7 or -C6H5. The obtained hydrophobic activated carbon consists of two parts: a core (activated carbon) and a shell (hydrophobic and breathable silica shell layer).
[0019] Wherein, in step (2), the siloxane is one of trimethylethoxysilane, triethylethoxysilane, propyltrimethoxysilane, phenyltrimethoxysilane and phenyltriethoxysilane.
[0020] Wherein, in step (2), the mass volume ratio of the intermediate product to siloxane is 1 g: 1-2 mL.
[0021] Wherein, in step (3), the solvent is ethanol or deionized water, and the silane is 3-mercaptopropyltrimethoxysilane or the like.
[0022] Compared with directly grafting hydrophobic groups on activated carbon, first, the activated carbon of the present invention has more abundant silanol groups as grafting sites because it is coated with a layer of silica shell, and Si-O-Si is more stable than CO-Si, which greatly improves the grafting rate of hydrophobic groups, has better hydrophobicity, and has better long-term effectiveness. Second, the present invention controls the reaction conditions, including the amount of tetraethyl orthosilicate added, the reaction time, and the reaction temperature, and first hydrolyzes tetraethyl orthosilicate to form silanol monomers by acid and then alkali, and then polymerizes on the outer layer of activated carbon. This method can make the polymer film more uniformly coated on the activated carbon on the one hand, and on the other hand, it can obtain a low-density Si-O-Si porous structure), thereby greatly reducing the impact on the internal microporous structure, pore characteristics and specific surface area of the activated carbon.
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: (1) Compared with directly grafting hydrophobic groups, the hydrophobicity of the core-shell hydrophobic activated carbon of the present invention is more stable and the grafting rate is also higher, so it has a longer-lasting hydrophobic performance; (2) The present invention has little effect on the microporous structure, pore characteristics and specific surface area inside the activated carbon, retains the excellent adsorption performance of the original activated carbon, and the change in specific surface area before and after modification is less than 10%; (3) Compared with the unmodified, the hydrophobic activated carbon prepared by the present invention has a significantly better adsorption capacity for organic matter and pigments in water or under a relative humidity of 99% than the original activated carbon. (4) Compared with pure hydrophobically modified activated carbon, the activated carbon of the present invention has a partial hydrophilic group grafted, which avoids the problem of complete rejection of the aqueous solution and resulting in failure to adsorb. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the SEM image of the hydrophobically modified activated carbon in Example 1 (b is a partial enlarged view of a);
[0025] Figure 2This is the EDS image of the hydrophobically modified activated carbon in Example 1;
[0026] Figure 3 The nitrogen adsorption-desorption curves of the activated carbon before and after modification in Example 1;
[0027] Figure 4 The pore size distribution of the activated carbon before and after modification in Example 1;
[0028] Figure 5 This is a comparison chart of the hydrophobicity of activated carbon in Example 1 (a is the original activated carbon, b is the intermediate product, and c is the hydrophobic activated carbon);
[0029] Figure 6 The contact angle comparison diagram of activated carbon in Example 1 (a is before modification, b is after modification);
[0030] Figure 7 The performance of activated carbon before and after modification in Example 1 in adsorbing styrene;
[0031] Figure 8 The performance of the activated carbon in Example 1 before and after modification when adsorbing methylene blue (qualitative analysis, a is before modification, b is after modification; c and d are comparisons between Example 1 and Comparative Example 1);
[0032] Fig. 9 The performance (quantitative analysis) of the activated carbon before and after modification in Example 1 when adsorbing methylene blue;
[0033] Fig.10 is the water contact angle of the modified activated carbon in Example 2;
[0034] Fig.11 is the water contact angle of the modified activated carbon in Example 3;
[0035] Fig.12 is the water contact angle of the modified activated carbon in Example 4;
[0036] Fig.13 is the water contact angle of the modified activated carbon in Example 5;
[0037] Fig.14 is the water contact angle of the modified activated carbon in Example 6;
[0038] Fig.15 is the water contact angle of the modified activated carbon in Example 7;
[0039] Fig.16 This is a comparison chart of the hydrophobicity of activated carbon in Example 8 (a is original, b is modified);
[0040] Fig.17The performance of the activated carbon in Example 1 and the activated carbon in Comparative Example 3 when adsorbing methylene blue (a is Comparative Example 3, b is Example 1). DETAILED DESCRIPTION
[0041] Example 1
[0042] The method for preparing the core-shell hydrophobically modified activated carbon of the present invention comprises the following steps:
[0043] (1) The powdered activated carbon is heated at 120°C for 5 hours until the quality is stable, the bound water and adsorbed impurities are removed, and the powdered activated carbon is stored for later use;
[0044] (2) At room temperature, 1 g of activated carbon was mixed with 80 g of anhydrous ethanol. After mixing, ultrasonic treatment was performed for 10 min to clean and disperse the activated carbon to ensure the cleanliness and uniformity of the activated carbon surface. Then, 1 mL of tetraethyl orthosilicate was added, and hydrochloric acid was added to adjust the pH to 5. The mixture was stirred at 450 r / min and 50° C. for 30 min. Ammonia water was then added to adjust the pH to 8. The mixture was stirred for 1 h to obtain suspension A.
[0045] (3) centrifuging the suspension A at a speed of 11000 r / min to obtain solid A, washing it three times with ethanol and deionized water respectively, and drying it overnight under vacuum at 150° C. to obtain an intermediate product coated with a hydrophilic silica shell layer;
[0046] (4) 1 g of solid A was mixed with 80 g of anhydrous ethanol, 1 mL of propyltrimethoxysilane was added to the solution, and the mixture was stirred at 50 °C for 12 h to obtain a suspension B;
[0047] (5) centrifuging the suspension B at a speed of 11000 r / min, washing the solid obtained after centrifugation with ethanol and deionized water three times respectively, and drying it under vacuum at 150° C. overnight to obtain hydrophobically modified activated carbon;
[0048] (6) 1 mL of mercaptosilane and 1 g of the activated carbon prepared in step (5) were added to 80 mL of ethanol, and the mixture was reacted at 50° C. for 3 h. A drop of 30 wt % hydrogen peroxide was added thereto, and the mixture was reacted at 50° C. for 6 h. The mixture was centrifuged, washed alternately with ethanol and water three times, and dried at 150° C. overnight to obtain the final product.
[0049] like Figures 1-2 As shown, the hydrophobically modified activated carbon prepared in Example 1 exhibits an obvious Si layer under a transmission electron microscope, indicating the successful construction of the silica shell layer. The hydrophobically modified activated carbon floats on the water surface, indicating that trimethylethoxysilane is successfully grafted onto the outer surface of the silica shell layer.
[0050] The original activated carbon and modified activated carbon in this example were subjected to nitrogen adsorption and desorption tests to evaluate their specific surface area and pore size. Figure 3 are the nitrogen adsorption-desorption curves before and after modification. Figure 4 is the pore size distribution before and after modification.
[0051] Table 1 shows the specific surface area and pore structure of the original activated carbon, intermediate activated carbon, and modified activated carbon. It can be seen from Table 1 that the BET area of the original activated carbon is 1294m 2 g -1 In comparison, the specific surface area of the intermediate activated carbon in Example 1 hardly decreased, and the BET specific surface area of the hydrophobically modified activated carbon did not decrease significantly, which was 1223 m 2 g -1 , only decreased by 5.5%. Combined with the pore size distribution, the hydrophobically modified activated carbon basically retains the adsorption performance of the original activated carbon under dry conditions. 2 g -1 , but this change is not negative, but a further optimization of the characteristics of activated carbon. The reduction in BET specific surface area may be due to the fine-tuning of the micropore structure during the modification process, but this does not change the superior adsorption capacity of activated carbon. While reducing the BET specific surface area, activated carbon obtains stronger hydrophobicity, which means that it can more effectively adsorb target substances in specific applications and show higher adsorption selectivity. The hydrophobic modified activated carbon prepared in this embodiment can be used for the adsorption of organic matter in industrial wastewater and the adsorption of volatile organic compounds in high humidity environments.
[0052] Table 1 Specific surface area and porous properties of activated carbon before and after modification
[0053]
[0054] The hydrophobicity of the original powdered activated carbon (before modification), the intermediate product activated carbon, and the hydrophobically modified activated carbon of Example 1 was tested to evaluate their surface hydrophobic properties in liquid media. First, 1 g of the original powdered activated carbon, the intermediate product activated carbon, and the hydrophobically modified activated carbon were taken respectively. These samples exhibited completely different behaviors when in contact with water, such as Figure 5 As shown in a. Once the original powdered activated carbon sample is placed in water, it is quickly partially wetted, and some of the activated carbon even quickly sinks to the bottom of the water. This phenomenon shows that the surface hygroscopicity of the original powdered activated carbon is high and cannot effectively resist water erosion. The surface hydrophilicity of the activated carbon coated with a hydrophilic silica shell is significantly enhanced. After the activated carbon is placed on the water surface, it can be quickly infiltrated by water and evenly dispersed throughout the water body, as shown in Figure 5b. The modified hydrophobic activated carbon samples showed unusual hydrophobic properties. The micro-powdered modified activated carbon formed a hydrophobic shell on its surface, which enabled it to float on the water surface for a long time (>30 days) without sinking to the bottom of the water quickly. This hydrophobic shell gives it unique surface properties, making it show good hydrophobic properties in water.
[0055] The hydrophobically modified activated carbon of Example 1 and the activated carbon before modification were tested for moisture absorption. The original activated carbon and the hydrophobically modified activated carbon samples were heated and dried in a 100°C drying oven for 1 hour to remove any existing moisture until the mass of the sample remained constant, which was the initial mass. The temperature of the constant temperature and humidity chamber was set to room temperature 25°C and relative humidity 99%, and the pretreated hydrophobically modified activated carbon and the original activated carbon samples were placed in glass containers, respectively, and sealed to prevent external moisture from entering. The samples were taken out after 24 hours and the mass of the samples was measured using a precision balance. Compared with the initial mass, the increased mass of the activated carbon sample is the absorbed moisture. The moisture absorption was calculated using the following formula: Moisture absorption = (weight gain-initial mass) / initial mass. The original activated carbon gained 55.4%, while the hydrophobically modified activated carbon gained 7.3%. Therefore, the moisture resistance of the hydrophobically modified activated carbon is better.
[0056] The contact angle test was performed on the hydrophobically modified activated carbon of Example 1 and the activated carbon before modification. The original activated carbon was hydrophilic and water droplets would spread out; while the contact angle of the modified activated carbon was 135°. Figure 6 shown.
[0057] The hydrophobically modified activated carbon prepared in Example 1 and the original activated carbon were subjected to styrene adsorption test. 1 g of the activated carbon before and after modification were taken, respectively, and placed in a 50 mg / L styrene aqueous solution. 0.5 mL of the sample was taken at 0, 3, 6, and 12 h, and 0.5 mL of the 50 mg / L styrene aqueous solution was added at the same time. The COD value of the sample was measured according to Figure 7 It can be seen that after adsorption by hydrophobically modified activated carbon, the COD value of the solution is lower, indicating that the hydrophobically modified activated carbon has better adsorption performance in water and also has good regeneration performance.
[0058] Weigh the same mass of original activated carbon and hydrophobically modified activated carbon, place them in a methylene blue solution (100 mg / L) of the same concentration, and take samples regularly to observe the color depth of the solution. Figure 8 As shown in the figure, after adsorption by hydrophobically modified activated carbon, the color of the solution is lighter, proving that hydrophobic modification can reduce the interference of water molecules on the adsorption of organic matter by activated carbon in water, and thus can improve the adsorption effect of methylene blue in water. In addition, the concentration of methylene blue in the solution was quantitatively analyzed, and the solution concentration was obtained by ultraviolet spectrophotometer, such as Fig. 9As shown in the figure, the concentration of methylene blue solution adsorbed by modified activated carbon is lower. After 1 hour of adsorption, the modified activated carbon basically adsorbed the methylene blue completely, and the solution concentration almost dropped to 0, while after 4 hours of adsorption by unmodified activated carbon, there was still a lot of methylene blue residue, with a concentration of 25 mg / L.
[0059] Comparative Example 1
[0060] Comparative Example 1 is a three-dimensional hydrophobic modified activated carbon.
[0061] (1) Powdered activated carbon was firstly placed in distilled water for ultrasonic cleaning for 10 minutes, then soaked in a pretreatment activation solution for 5 minutes, and then dried in a 100°C oven for 12 hours; the pretreatment activation solution was an ammonia solution with a pH value of 8 to 9;
[0062] (2) Add 9.8 parts by mass of ethyltrichlorosilane to 50 parts by mass of n-hexane, n-butane, n-pentane, or toluene, stir evenly, and then add 11 parts by mass of activated carbon; transfer the conical flask containing the activated carbon directly to an ultrasonic environment for immersion reaction for 4 hours, with an ultrasonic power of 250 W and an ultrasonic frequency of 20 kHz;
[0063] (3) After the reaction is completed, the activated carbon is taken out and washed with acetone three times; the washed activated carbon is placed in a vacuum drying oven and dried at 150° C. for 8 h to obtain a three-dimensional hydrophobic modified activated carbon.
[0064] Comparative Example 1: The contact angle of the three-dimensional hydrophobic modified activated hydrophobic activated carbon is 113° and the specific surface area is 816.34 m 2 g -1 .
[0065] Weigh the same mass of activated carbon from Example 1 and activated carbon from Comparative Example 1, place them in a methylene blue solution (100 mg / L) of the same concentration, and take samples at regular intervals to observe the color depth of the solution. Figure 8 As shown in c and d, after adsorption by the modified activated carbon in Example 1, the solution color is lighter, proving that the modification method used in Example 1 is more effective. In addition, the concentration of methylene blue in the solution was quantitatively analyzed, and the solution concentration was obtained by ultraviolet spectrophotometer. The results are shown in Table 2, and the concentration of methylene blue solution adsorbed by the modified activated carbon in Example 1 is lower. After 1h of adsorption, the modified activated carbon basically adsorbs the methylene blue clean, and the solution concentration is almost reduced to 0, while the activated carbon obtained in Comparative Example 1 still has more methylene blue residues after 3h of adsorption, with a concentration of 16mg / L.
[0066] Table 2. Adsorption effect of Example 1 and Comparative Example 1 on methylene blue (solution concentration mg / L)
[0067]
[0068] Compared with Example 1, the biggest difference of Comparative Example 1 is that there is no coating of the silica shell. Comparative Example 1 directly uses the limited hydroxyl groups on the carbon to graft the hydrophobic group, while the silica shell of Example 1 provides more abundant hydroxyl sites, so the grafting success rate is higher and the hydrophobic performance is better. Second, the Si-O-Si bond is more stable than the CO-Si bond, which makes the hydrophobicity of the modified activated carbon obtained in Example 1 more durable and long-lasting, and can remain non-sinking for 30 days, while the activated carbon obtained in Comparative Example 1 basically settles to the bottom of the water after one week. Third, in Example 1, the hydrophobic group is directly grafted onto the external silica shell, which has little effect on the internal pore size and specific surface area of the activated carbon; while in Comparative Example 1, the hydrophobic group easily enters the interior of the activated carbon, blocks the pores, affects its structural parameters, and greatly reduces the specific surface area. Fourth, due to the presence of the hydrophilic silica shell, the aqueous solution is more likely to contact the surface of the activated carbon. If it is purely hydrophobic activated carbon, water will be repelled and the pigments dissolved in the water will be difficult to be adsorbed and removed by the activated carbon. In addition, the hydrophilic shell can attract the aqueous solution to the surface of the activated carbon. Due to the presence of hydrophobic groups, water cannot enter the interior of the activated carbon, and the pollutants enter the internal pores of the activated carbon, thereby greatly improving the removal rate of pollutants in the water.
[0069] Example 2
[0070] The method for preparing the core-shell hydrophobically modified activated carbon of the present invention comprises the following steps:
[0071] (1) The powdered activated carbon is heated at 120°C for 5 hours until the quality is stable, the bound water and adsorbed impurities are removed, and the powdered activated carbon is stored for later use;
[0072] (2) At room temperature, 1 g of activated carbon was mixed with 80 g of anhydrous ethanol. After mixing, ultrasonic treatment was performed for 10 min to clean and disperse the activated carbon to ensure the cleanliness and uniformity of the activated carbon surface. Then, 1 mL of tetraethyl orthosilicate was added, and hydrochloric acid was added to adjust the pH to 5. The mixture was stirred at 450 r / min and 50° C. for 30 min. Ammonia water was then added to adjust the pH to 8. The mixture was stirred for 1 h to obtain suspension A.
[0073] (3) centrifuging the suspension A at a speed of 11000 r / min to obtain solid A, washing it three times with ethanol and deionized water respectively, and drying it overnight under vacuum at 150° C.;
[0074] (4) 1 g of solid A was mixed with 80 g of anhydrous ethanol, 1.5 mL of propyltrimethoxysilane was added to the solution, and the mixture was stirred at 50 °C for 1 h to obtain a suspension B;
[0075] (5) centrifuging the suspension B at a speed of 11000 r / min, washing the solid obtained after centrifugation with ethanol and deionized water three times respectively, and drying it under vacuum at 150° C. overnight to obtain hydrophobically modified activated carbon;
[0076] (6) 1 mL of mercaptosilane and 1 g of the activated carbon prepared in step (5) were added to 80 mL of ethanol, and the mixture was reacted at 50° C. for 3 h. A drop of 30 wt % hydrogen peroxide was added thereto, and the mixture was reacted at 50° C. for 6 h. The mixture was centrifuged, washed alternately with ethanol and water three times, and dried at 150° C. overnight to obtain the final product.
[0077] Table 3 shows the specific surface area and pore structure of the hydrophobically modified activated carbon obtained in Example 2. It can be seen from Table 3 that the BET area of the original activated carbon is 1294 m 2 g -1 In comparison, the BET specific surface area of the hydrophobically modified activated carbon in Example 2 did not decrease significantly, which was 1197 m 2 g -1 , only decreased by 7.5%. Combined with the pore size distribution, the hydrophobically modified activated carbon basically retains the adsorption performance of the original activated carbon under dry conditions.
[0078] Table 3 Specific surface area and porous properties of activated carbon before and after modification
[0079]
[0080] The hydrophobically modified activated carbon of Example 2 and the activated carbon before modification were tested for moisture absorption. The original activated carbon and the hydrophobically modified activated carbon samples were heated and dried in a 100°C drying oven for 1 hour to remove any existing moisture until the mass of the sample remained constant, which was the initial mass. The temperature of the constant temperature and humidity chamber was set to room temperature 25°C and relative humidity 99%, and the pretreated hydrophobically modified activated carbon and the original activated carbon samples were placed in glass containers, respectively, and sealed to prevent external moisture from entering. The samples were taken out after 24 hours and the mass of the samples was measured using a precision balance. Compared with the initial mass, the increased mass of the activated carbon sample is the absorbed moisture. The moisture absorption was calculated using the following formula: Moisture absorption = (weight gain-initial mass) / initial mass. The original activated carbon gained 55.4%, while the hydrophobically modified activated carbon gained 4.9%. Therefore, the moisture resistance of the hydrophobically modified activated carbon is better.
[0081] The contact angle test of the hydrophobically modified activated carbon in Example 2 showed that the water contact angle was 142°. Fig.10 shown.
[0082] Example 3
[0083] The method for preparing the core-shell hydrophobically modified activated carbon of the present invention comprises the following steps:
[0084] (1) The powdered activated carbon is heated at 120°C for 5 hours until the quality is stable, the bound water and adsorbed impurities are removed, and the powdered activated carbon is stored for later use;
[0085] (2) At room temperature, 1 g of activated carbon was mixed with 80 g of anhydrous ethanol. After mixing, ultrasonic treatment was performed for 10 min to clean and disperse the activated carbon to ensure the cleanliness and uniformity of the activated carbon surface. Then, 1 mL of tetraethyl orthosilicate was added, and hydrochloric acid was added to adjust the pH to 5. The mixture was stirred at 450 r / min and 50° C. for 30 min. Ammonia water was then added to adjust the pH to 8. The mixture was stirred for 1 h to obtain suspension A.
[0086] (3) centrifuging the suspension A at a speed of 11000 r / min to obtain solid A, washing it three times with ethanol and deionized water respectively, and drying it overnight under vacuum at 150° C.;
[0087] (4) 1 g of solid A was mixed with 80 g of anhydrous ethanol, 2 mL of propyltrimethoxysilane was added to the solution, and the mixture was stirred at 50 °C for 12 h to obtain a suspension B;
[0088] (5) centrifuging the suspension B at a speed of 11000 r / min, washing the solid obtained after centrifugation with ethanol and deionized water three times respectively, and drying it under vacuum at 150° C. overnight to obtain hydrophobically modified activated carbon;
[0089] (6) 1 mL of mercaptosilane and 1 g of the activated carbon prepared in step (5) were added to 80 mL of ethanol, and the mixture was reacted at 50° C. for 3 h. A drop of 30 wt % hydrogen peroxide was added thereto, and the mixture was reacted at 50° C. for 6 h. The mixture was centrifuged, washed alternately with ethanol and water three times, and dried at 150° C. overnight to obtain the final product.
[0090] Table 4 shows the specific surface area and pore structure of the hydrophobically modified activated carbon obtained in Example 3. It can be seen from Table 4 that the BET area of the original activated carbon is 1294 m 2 g -1 In comparison, the BET specific surface area of the hydrophobically modified activated carbon in Example 2 did not decrease significantly, which was 1178 m 2 g -1 , only decreased by 9.9%. Combined with the pore size distribution, the hydrophobically modified activated carbon basically retained the adsorption performance of the original activated carbon under dry conditions.
[0091] Table 4 Specific surface area and porous properties of activated carbon before and after modification
[0092]
[0093] The hydrophobically modified activated carbon of Example 3 and the activated carbon before modification were tested for moisture absorption. The original activated carbon and the hydrophobically modified activated carbon samples were heated and dried in a 100°C drying oven for 1 hour to remove any existing moisture until the mass of the sample remained constant, which was the initial mass. The temperature of the constant temperature and humidity chamber was set to room temperature 25°C and relative humidity 99%, and the pretreated hydrophobically modified activated carbon and the original activated carbon samples were placed in glass containers, respectively, and sealed to prevent external moisture from entering. The samples were taken out after 24 hours and the mass of the samples was measured using a precision balance. Compared with the initial mass, the increased mass of the activated carbon sample is the absorbed moisture. The moisture absorption was calculated using the following formula: Moisture absorption = (weight gain-initial mass) / initial mass. The original activated carbon gained 55.4%, while the hydrophobically modified activated carbon gained 4.2%. Therefore, the moisture resistance of the hydrophobically modified activated carbon is better.
[0094] The contact angle test was performed on the hydrophobically modified activated carbon of Example 3. Its water contact angle was 145°. Fig.11 shown.
[0095] Example 4
[0096] The method for preparing the core-shell hydrophobically modified activated carbon of the present invention comprises the following steps:
[0097] (1) The powdered activated carbon is heated at 120°C for 5 hours until the quality is stable, the bound water and adsorbed impurities are removed, and the powdered activated carbon is stored for later use;
[0098] (2) At room temperature, 1 g of activated carbon was mixed with 80 g of anhydrous ethanol. After mixing, ultrasonic treatment was performed for 10 min to clean and disperse the activated carbon to ensure the cleanliness and uniformity of the activated carbon surface. Then, 1 mL of tetraethyl orthosilicate was added, and hydrochloric acid was added to adjust the pH to 5. The mixture was stirred at 450 r / min and 50° C. for 30 min. Ammonia water was then added to adjust the pH to 8. The mixture was stirred for 1 h to obtain suspension A.
[0099] (3) centrifuging the suspension A at a speed of 11000 r / min to obtain solid A, washing it three times with ethanol and deionized water respectively, and drying it overnight under vacuum at 150° C.;
[0100] (4) 1 g of solid A was mixed with 80 g of anhydrous ethanol, 1 mL of trimethylethoxysilane was added to the solution, and the mixture was stirred at 50 °C for 12 h to obtain a suspension B;
[0101] (5) centrifuging the suspension B at a speed of 11000 r / min, washing the solid obtained after centrifugation with ethanol and deionized water three times respectively, and drying it under vacuum at 150° C. overnight to obtain hydrophobically modified activated carbon;
[0102] (6) 1 mL of mercaptosilane and 1 g of the activated carbon prepared in step (5) were added to 80 mL of ethanol, and the mixture was reacted at 50° C. for 3 h. A drop of 30 wt % hydrogen peroxide was added thereto, and the mixture was reacted at 50° C. for 6 h. The mixture was centrifuged, washed alternately with ethanol and water three times, and dried at 150° C. overnight to obtain the final product.
[0103] The hydrophobically modified activated carbon of Example 4 and the activated carbon before modification were tested for moisture absorption. The original activated carbon and the hydrophobically modified activated carbon samples were heated and dried in a 100°C drying oven for 1 hour to remove any existing moisture until the mass of the sample remained constant, which was the initial mass. The temperature of the constant temperature and humidity chamber was set to room temperature 25°C and relative humidity 99%, and the pretreated hydrophobically modified activated carbon and the original activated carbon samples were placed in glass containers, respectively, and sealed to prevent external moisture from entering. The samples were taken out after 24 hours, and the mass of the samples was measured using a precision balance. Compared with the initial mass, the increased mass of the activated carbon sample is the absorbed moisture. The moisture absorption was calculated using the following formula: Moisture absorption = (weight gain-initial mass) / initial mass. The original activated carbon gained weight by 55.4%, while the hydrophobically modified activated carbon gained weight by 9.2%.
[0104] The contact angle test was performed on the hydrophobically modified activated carbon of Example 4. Its water contact angle was 134°. Fig.12 shown.
[0105] Example 5
[0106] The method for preparing the core-shell hydrophobically modified activated carbon of the present invention comprises the following steps:
[0107] (1) The powdered activated carbon is heated at 120°C for 5 hours until the quality is stable, the bound water and adsorbed impurities are removed, and the powdered activated carbon is stored for later use;
[0108] (2) At room temperature, 1 g of activated carbon was mixed with 80 g of anhydrous ethanol. After mixing, ultrasonic treatment was performed for 10 min to clean and disperse the activated carbon to ensure the cleanliness and uniformity of the activated carbon surface. Then, 1 mL of tetraethyl orthosilicate was added, and hydrochloric acid was added to adjust the pH to 5. The mixture was stirred at 450 r / min and 50° C. for 30 min. Ammonia water was then added to adjust the pH to 8. The mixture was stirred for 1 h to obtain suspension A.
[0109] (3) centrifuging the suspension A at a speed of 11000 r / min to obtain solid A, washing it three times with ethanol and deionized water respectively, and drying it overnight under vacuum at 150° C.;
[0110] (4) 1 g of solid A was mixed with 80 g of anhydrous ethanol, 1 mL of phenyltrimethoxysilane was added to the solution, and the mixture was stirred at 50 °C for 12 h to obtain a suspension B;
[0111] (5) centrifuging the suspension B at a speed of 11000 r / min, washing the solid obtained after centrifugation with ethanol and deionized water three times respectively, and drying it under vacuum at 150° C. overnight to obtain hydrophobically modified activated carbon;
[0112] (6) 1 mL of mercaptosilane and 1 g of the activated carbon prepared in step (5) were added to 80 mL of ethanol, and the mixture was reacted at 50° C. for 3 h. A drop of 30 wt % hydrogen peroxide was added thereto, and the mixture was reacted at 50° C. for 6 h. The mixture was centrifuged, washed alternately with ethanol and water three times, and dried at 150° C. overnight to obtain the final product.
[0113] The hydrophobically modified activated carbon of Example 5 and the activated carbon before modification were tested for moisture absorption. The original activated carbon and the hydrophobically modified activated carbon samples were heated and dried in a 100°C drying oven for 1 hour to remove any existing moisture until the mass of the sample remained constant, which was the initial mass. The temperature of the constant temperature and humidity chamber was set to room temperature 25°C and relative humidity 99%, and the pretreated hydrophobically modified activated carbon and the original activated carbon samples were placed in glass containers, respectively, and sealed to prevent external moisture from entering. The samples were taken out after 24 hours and the mass of the samples was measured using a precision balance. Compared with the initial mass, the increased mass of the activated carbon sample is the absorbed moisture. The moisture absorption was calculated using the following formula: Moisture absorption = (weight gain-initial mass) / initial mass. The original activated carbon gained 55.4% in weight, while the hydrophobically modified activated carbon gained 11.8% in weight.
[0114] The contact angle test was performed on the hydrophobically modified activated carbon of Example 5. Its water contact angle was 130°. Fig.13 The grafting rate of the hydrophobic group of phenylsilane in the hydrophobically modified activated carbon of Example 5 is lower than the grafting rate of the hydrophobic group of propylsilane in Example 1.
[0115] Example 6
[0116] The method for preparing the core-shell hydrophobically modified activated carbon of the present invention comprises the following steps:
[0117] (1) The powdered activated carbon is heated at 120°C for 5 hours until the quality is stable, the bound water and adsorbed impurities are removed, and the powdered activated carbon is stored for later use;
[0118] (2) At room temperature, 1 g of activated carbon was mixed with 100 g of deionized water, and then ultrasonicated for 10 min to clean and disperse the activated carbon to ensure the cleanliness and uniformity of the activated carbon surface; then 1 mL of ethyl orthosilicate was added, and hydrochloric acid was added to adjust the pH to 6, and stirred at 450 r / min and 60° C. for 30 min, and then ammonia water was added to adjust the pH to 8, and stirring was continued for 1 h to obtain suspension A;
[0119] (3) centrifuging the suspension A at a speed of 11000 r / min to obtain solid A, washing it three times with ethanol and deionized water respectively, and drying it overnight under vacuum at 175°C;
[0120] (4) 1 g of solid A was mixed with 100 g of deionized water, 0.4 g of DuPont surfactant was added, and 1 mL of propyltrimethoxysilane was added to the solution. The mixture was stirred at 60 °C for 12 h to obtain suspension B.
[0121] (5) centrifuging the suspension B at a speed of 11000 r / min, washing the solid obtained after centrifugation with ethanol and deionized water three times respectively, and drying it under vacuum at 175° C. overnight to obtain hydrophobically modified activated carbon;
[0122] (6) 1 mL of mercaptosilane and 1 g of the activated carbon prepared in step (5) were added to 80 mL of ethanol, and the mixture was reacted at 50° C. for 3 h. A drop of 30 wt % hydrogen peroxide was added thereto, and the mixture was reacted at 50° C. for 6 h. The mixture was centrifuged, washed alternately with ethanol and water three times, and dried at 150° C. overnight to obtain the final product.
[0123] The hydrophobically modified activated carbon of Example 6 and the activated carbon before modification were tested for moisture absorption. The original activated carbon and the hydrophobically modified activated carbon samples were heated and dried in a 100°C drying oven for 1 hour to remove any existing moisture until the mass of the sample remained constant, which was the initial mass. The temperature of the constant temperature and humidity chamber was set to room temperature 25°C and relative humidity 99%, and the pretreated hydrophobically modified activated carbon and the original activated carbon samples were placed in glass containers, respectively, and sealed to prevent external moisture from entering. The samples were taken out after 24 hours and the mass of the samples was measured using a precision balance. Compared with the initial mass, the increased mass of the activated carbon sample is the absorbed moisture. The moisture absorption was calculated using the following formula: Moisture absorption = (weight gain-initial mass) / initial mass. The original activated carbon gained 55.4% in weight, while the hydrophobically modified activated carbon gained 15.0%.
[0124] The contact angle test of the hydrophobically modified activated carbon in Example 6 showed that the water contact angle was 130°. Fig.14 shown.
[0125] Example 7
[0126] The method for preparing the core-shell hydrophobically modified activated carbon of the present invention comprises the following steps:
[0127] (1) The powdered activated carbon is heated at 120°C for 5 hours until the quality is stable, the bound water and adsorbed impurities are removed, and the powdered activated carbon is stored for later use;
[0128] (2) At room temperature, 1 g of activated carbon was mixed with 100 g of deionized water, and then ultrasonicated for 10 min to clean and disperse the activated carbon to ensure the cleanliness and uniformity of the activated carbon surface; then 1 mL of ethyl orthosilicate was added, and hydrochloric acid was added to adjust the pH to 6, and stirred at 450 r / min and 60° C. for 30 min, and then ammonia water was added to adjust the pH to 8, and stirring was continued for 1 h to obtain suspension A;
[0129] (3) centrifuging the suspension A at a speed of 11000 r / min to obtain solid A, washing it three times with ethanol and deionized water respectively, and drying it overnight under vacuum at 175°C;
[0130] (4) 1 g of solid A was mixed with 100 g of deionized water, 0.4 g of Liou surfactant was added, and 1 mL of propyltrimethoxysilane was added to the solution. The mixture was stirred at 60 °C for 12 h to obtain suspension B;
[0131] (5) centrifuging the suspension B at a speed of 11000 r / min, washing the solid obtained after centrifugation with ethanol and deionized water three times respectively, and drying it under vacuum at 175° C. overnight to obtain hydrophobically modified activated carbon;
[0132] (6) 1 mL of mercaptosilane and 1 g of the activated carbon prepared in step (5) were added to 80 mL of ethanol, and the mixture was reacted at 50° C. for 3 h. A drop of 30 wt % hydrogen peroxide was added thereto, and the mixture was reacted at 50° C. for 6 h. The mixture was centrifuged, washed alternately with ethanol and water three times, and dried at 150° C. overnight to obtain the final product.
[0133] The hydrophobically modified activated carbon of Example 7 and the activated carbon before modification were tested for moisture absorption. The original activated carbon and the hydrophobically modified activated carbon samples were heated and dried in a 100°C drying oven for 1 hour to remove any existing moisture until the mass of the sample remained constant, which was the initial mass. The temperature of the constant temperature and humidity chamber was set to room temperature 25°C and relative humidity 99%, and the pretreated hydrophobically modified activated carbon and the original activated carbon samples were placed in glass containers, respectively, and sealed to prevent external moisture from entering. The samples were taken out after 24 hours, and the mass of the samples was measured using a precision balance. Compared with the initial mass, the increased mass of the activated carbon sample is the absorbed moisture. The moisture absorption was calculated using the following formula: Moisture absorption = (weight gain-initial mass) / initial mass. The original activated carbon gained 55.4% in weight, while the hydrophobically modified activated carbon gained 21.8% in weight.
[0134] The contact angle test of the hydrophobically modified activated carbon of Example 7 showed that the water contact angle was 121°. Fig.15 shown.
[0135] The hydrophobicity of the hydrophobically modified activated carbon obtained in Examples 6 and 7 is not as good as that in Example 1. The reason is that the solvent system used in Examples 6 and 7 is aqueous, while the solvent used in Example 1 is ethanol. The dispersibility of silane in aqueous solvents is not as good as ethanol, so that the grafting rate of hydrophobic groups in Examples 6 and 7 is lower than that in Example 1.
[0136] Example 8
[0137] The method for preparing the core-shell hydrophobically modified activated carbon of the present invention comprises the following steps:
[0138] (1) The columnar activated carbon is heated at 120°C for 5 hours until the quality is stable, the bound water and adsorbed impurities are removed, and the activated carbon is stored for later use;
[0139] (2) At room temperature, 1 g of activated carbon was mixed with 80 g of anhydrous ethanol. After mixing, ultrasonic treatment was performed for 10 min to clean and disperse the activated carbon to ensure the cleanliness and uniformity of the activated carbon surface. Then, 1 mL of tetraethyl orthosilicate was added, and hydrochloric acid was added to adjust the pH to 5. The mixture was stirred at 450 r / min and 50° C. for 30 min. Ammonia water was then added to adjust the pH to 8. The mixture was stirred for 1 h to obtain suspension A.
[0140] (3) centrifuging the suspension A at a speed of 11000 r / min to obtain solid A, washing it three times with ethanol and deionized water respectively, and drying it overnight under vacuum at 150° C.;
[0141] (4) 1 g of solid A was mixed with 80 g of anhydrous ethanol, 1 mL of propyltrimethoxysilane was added to the solution, and the mixture was stirred at 50 °C for 12 h to obtain a suspension B;
[0142] (5) centrifuging the suspension B at a speed of 11000 r / min, washing the solid obtained after centrifugation with ethanol and deionized water three times respectively, and drying it under vacuum at 150° C. overnight to obtain hydrophobically modified activated carbon;
[0143] (6) 1 mL of mercaptosilane and 1 g of the activated carbon prepared in step (5) were added to 80 mL of ethanol, and the mixture was reacted at 50° C. for 3 h. A drop of 30 wt % hydrogen peroxide was added thereto, and the mixture was reacted at 50° C. for 6 h. The mixture was centrifuged, washed alternately with ethanol and water three times, and dried at 150° C. overnight to obtain the final product.
[0144] The hydrophobicity of the original columnar activated carbon (before modification) and the hydrophobically modified activated carbon of Example 1 was tested to evaluate their surface hydrophobic properties in liquid media. First, 1 g of the original activated carbon and 1 g of the hydrophobically modified activated carbon were taken respectively. These samples exhibited completely different behaviors when in contact with water, such as Fig.16As shown. Once the original activated carbon sample is placed in water, it is quickly partially wetted, and some of the activated carbon even quickly sinks to the bottom of the water. This phenomenon shows that the surface hygroscopicity of the original activated carbon is high and cannot effectively resist water erosion. The modified hydrophobic activated carbon sample shows unusual hydrophobic properties. The modified activated carbon forms a hydrophobic shell on its surface, which enables it to float on the water surface for a long time (>30 days) without quickly sinking to the bottom of the water. This hydrophobic shell gives it unique surface properties, allowing it to exhibit good hydrophobic properties in water.
[0145] Comparative Example 2
[0146] A method for preparing hydrophobically modified activated carbon comprises the following steps:
[0147] (1) First, the powdered activated carbon is ultrasonically cleaned in distilled water for 10 minutes, then immersed in a pretreatment activation solution for 10 minutes, and then dried in a 150°C oven for 12 hours; the pretreatment activation solution is an ammonia solution with a pH value of 8 to 9;
[0148] (2) adding 10 parts by mass of propyltrichlorosilane to 30 parts by mass of n-hexane, stirring evenly, then adding 10 parts by mass of activated carbon, and immediately sealing the round-bottom flask; transferring the activated carbon to an ultrasonic environment for immersion reaction for 1 hour, with an ultrasonic power of 600 W and an ultrasonic frequency of 40 kHz;
[0149] (3) After the reaction is completed, the activated carbon is taken out and washed with n-hexane for 5 times; the washed activated carbon is placed in a vacuum drying oven and dried at 150° C. for 12 h to obtain hydrophobic modified activated carbon.
[0150] The contact angle of the hydrophobically modified activated carbon in Comparative Example 2 was measured. After measurement, the water contact angle of the hydrophobically modified activated carbon in Comparative Example 2 was 125°.
[0151] The hydrophobic modified activated carbon of comparative example 2 was tested for moisture absorption. The hydrophobic modified activated carbon sample of comparative example 2 was heated and dried in a drying oven at 100°C for 1 hour until the mass of the sample remained constant, and the temperature of the constant temperature and humidity chamber was set to room temperature 25°C and relative humidity 99%. The pretreated hydrophobic modified activated carbon was placed in a glass container and sealed to prevent external moisture from entering. The sample was taken out after 24 hours, and the mass of the sample was measured using a precision balance. It was measured that the weight gain of the hydrophobic modified activated carbon of comparative example 2 was 19.1%. Therefore, the moisture-proof performance of the hydrophobic modified activated carbon of Example 1 is better.
[0152] Comparative Example 3
[0153] A method for preparing hydrophobically modified activated carbon comprises the following steps:
[0154] (1) At room temperature, add activated carbon to hydrogen peroxide and soak for 1 hour, then take it out and dry it for later use;
[0155] (2) adding 0.1 parts by weight of hexadecyltrimethylammonium bromide to 100 parts by weight of deionized water, and stirring at 50° C. for 30 min; placing 1 part by weight of the activated carbon treated in step (1) in the hexadecyltrimethylammonium bromide aqueous solution and soaking it for 3 h, taking it out after soaking, rinsing it with clean water twice, and drying it for later use;
[0156] (3) 1 part by mass of silica sol with a pH value of 4, a particle size of 4 nm, and a solid content of 15% was added to deionized water, and ultrasonically mixed in an ultrasonic cleaning machine for 10 minutes, and then 80 mL of anhydrous ethanol was added thereto, and magnetically stirred for 20 minutes to mix evenly, and then 0.1 part by mass of tetraethyl orthosilicate was added and stirred continuously, and finally 0.1 part by mass of perfluorosiloxane was added dropwise using a pipette, and magnetically stirred for 24 hours under heating in a water bath at 50° C. to obtain a superhydrophobic emulsion;
[0157] (4) concentrating the super hydrophobic emulsion by rotary evaporation at 50° C. by 10 times, and then diluting it by 10 times with anhydrous ethanol, and repeating the process twice to obtain a moisture-proof modified emulsion, wherein the solute content in the moisture-proof modified emulsion is 10 times the solute content in the super hydrophobic emulsion;
[0158] (5) Add 1 part by mass of the activated carbon treated in step (2) into 10 parts by mass of moisture-proof modified emulsion and soak for 12 hours. Take it out after soaking, dry it, and then put it into a hydrochloric acid solution with a mass concentration of 10% and soak it for 2 hours. Take it out after soaking and dry it at 50°C for 6 hours to obtain hydrophobic modified activated carbon.
[0159] The hydrophobically modified activated carbon of Example 1 and the hydrophobically modified activated carbon of Comparative Example 3 were tested for their methylene blue adsorption performance. Activated carbons of the same mass were weighed and placed in a methylene blue solution of the same concentration (initial concentration was 100 mg / L). After 1 hour, the color depth of the solution was observed. Fig.17 As shown, the solution color is lighter after adsorption by modified activated carbon in Example 1. The concentration of methylene blue in the solution measured by ultraviolet spectrophotometer is less than 0.5 mg / L, and the removal rate is more than 99%, while the concentration of methylene blue in the solution in Comparative Example 3 is 17 mg / L, and the removal rate is 83%.
[0160] Comparative Example 4
[0161] (1) The powdered activated carbon is heated at 120°C for 5 hours until the quality is stable, the bound water and adsorbed impurities are removed, and the powdered activated carbon is stored for later use;
[0162] (2) At room temperature, 1 g of activated carbon was mixed with 100 g of deionized water, and then ultrasonicated for 10 min to clean and disperse the activated carbon to ensure the cleanliness and uniformity of the activated carbon surface; then 1 mL of ethyl orthosilicate was added, and hydrochloric acid was added to adjust the pH to 6, and stirred at 450 r / min and 60° C. for 30 min, and then ammonia water was added to adjust the pH to 8, and stirring was continued for 1 h to obtain suspension A;
[0163] (3) centrifuging the suspension A at a speed of 11000 r / min to obtain solid A, washing it three times with ethanol and deionized water respectively, and drying it overnight under vacuum at 175°C;
[0164] (4) 1 g of solid A was mixed with 100 g of deionized water, 0.4 g of DuPont surfactant was added, and 1 mL of propyltrimethoxysilane was added to the solution. The mixture was stirred at 60 °C for 12 h to obtain suspension B.
[0165] (5) The suspension B was centrifuged at a speed of 11000 r / min. The solid obtained after the centrifugation was washed three times with ethanol and deionized water respectively, and dried overnight at 175° C. under vacuum to obtain hydrophobically modified activated carbon.
[0166] The activated carbon obtained in Example 6 and the activated carbon in Comparative Example 4 were subjected to methylene blue adsorption to verify the importance of the last step of grafting hydrophilic groups. Weigh the same mass of the activated carbon in Example 6 and the activated carbon in Comparative Example 4, and place them in a methylene blue solution (100 mg / L) of the same concentration for adsorption. Both can be adsorbed cleanly, and the time required for complete adsorption of the activated carbon in Example 6 is 2.5 hours, while the time required for the activated carbon in Comparative Example 4 is 3 hours. The reasons are as follows: the activated carbon obtained in Comparative Example 4 has no further grafted hydrophilic groups, so it is placed in a methylene blue solution, and compared with the activated carbon in Example 6, it cannot be fully contacted with the solution, thereby prolonging its adsorption time for organic matter in the aqueous solution.
Claims
1. A core-shell hydrophobically modified activated carbon, characterized in that: It includes activated carbon and a porous shell layer of silicon dioxide wrapped around the activated carbon.
2. The method for preparing the core-shell hydrophobically modified activated carbon according to claim 1, characterized in that: The activated carbon is semi-hydrophobic modified, specifically comprising the following steps: (1) Construction of silica shell: The pretreated activated carbon is dispersed in a solvent, and ethyl orthosilicate is added thereto. The pH of the reaction solution is first adjusted to 5-6, and stirred at 450-500 r / min and 50-60° C. for 20-30 min. The pH of the reaction solution is then adjusted to 8-9, and stirring is continued for 0.5-1 h to obtain a suspension A. The suspension A is centrifuged to obtain a preliminarily modified activated carbon. The initially modified activated carbon is washed and dried to obtain an intermediate product coated with a hydrophilic silica shell; (2) Grafting of hydrophobic groups: dispersing the product obtained in step (1) in a solvent, adding siloxane thereto, and stirring thoroughly to obtain a suspension B; centrifuging the suspension B to obtain a hydrophobically modified activated carbon; The hydrophobically modified activated carbon can be washed and dried. (3) Grafting of hydrophilic groups: mercaptosilane and the product obtained in step (2) are added to a solvent, hydrogen peroxide is added after the reaction, and then centrifugation, washing and drying are performed to obtain the final product.
3. The preparation method according to claim 2, characterized in that: In step (1), the pretreatment of the activated carbon is: heating the activated carbon at not less than 120° C. for 5 to 8 hours.
4. The preparation method according to claim 2, characterized in that: In step (1), the intermediate product obtained is activated carbon coated with a hydrophilic silica shell layer.
5. The preparation method according to claim 2, characterized in that: In step (1) and step (2), the solvent is anhydrous ethanol, ethylene glycol or deionized water; when the solvent is deionized water, a surfactant is added to the solvent in an amount of 0.4 to 0.5% by mass of the solvent.
6. The preparation method according to claim 2, characterized in that: In step (1), the mass volume ratio of activated carbon to tetraethyl orthosilicate is 1 g: 1-2 mL.
7. The preparation method according to claim 2, characterized in that: In step (1), the reagents for adjusting pH are hydrochloric acid with a concentration of 0.1 mol / L and ammonia water with a mass fraction of 25-28%.
8. The preparation method according to claim 2, characterized in that: Step (2) is hydrophobic modification, in which the hydrophobic groups are directly grafted onto the hydrophilic silica shell layer, and the resulting hydrophobic shell layer is SiO2@-OSiR n , -R n It is one of -(CH3)3, -(C2H5)3, -C3H7 or -C6H5.
9. The preparation method according to claim 2, characterized in that: In step (2), the mass volume ratio of the intermediate product to the siloxane is 1 g: 1-2 mL.
10. The preparation method according to claim 2, characterized in that: In step (3), the solvent is ethanol or deionized water, and the mercaptosilane is 3-mercaptopropyltrimethoxysilane.
Citation Information
Cited By
Super-hydrophobic activated carbon adsorption material as well as preparation method and application thereof
CN119819263A
Activated carbon material for treating waste gas in high-humidity environment and preparation method of activated carbon material
CN121361794A
Preparation method and application of core-shell activated carbon-based hierarchical porous concrete internal curing agent
CN122426958A